Development and Evaluation of an AI-Integrated Project-Based Learning Model for Technical and Vocational Education - Abdul Habib Arrasyidi Desky; Muhammad Anwar; Wakhinuddin Simatupang; Refdinal Refdinal; Dedy Irfan; Muhammad Adri (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2026)
The rapid advancement of Artificial Intelligence (AI) technologies presents significant opportunities for transforming pedagogical approaches in Technical and Vocational Education and Training (TVET). This study describes the systematic development and empirical evaluation of an AI-Integrated Project-Based Learning (AI-PjBL) model designed to enhance technical competency, problem-solving skills, and digital literacy among vocational students. Using an educational design research methodology, the model was developed through iterative cycles of design, implementation, and evaluation. Participants consisted of 120 vocational students across two cohorts. Data were collected through competency assessments, student engagement surveys, and teacher observation rubrics. Results indicate statistically significant improvements in technical skill acquisition (p < 0.01), higher-order thinking, and collaborative performance compared to conventional instruction. The findings suggest that the AI-PjBL model offers a viable and scalable framework for modernising TVET curricula and preparing students for Industry 4.0 demands.